Effect of vitamin D analogues calcitriol and paricalcitol in a rat model of puromycin aminonucleoside-induced nephrotic syndrome - Hamdi Metin; Pelin Ertan; Ahmet KeskinoÄŸlu; Pembe KeskinoÄŸlu; Elgin Türköz Uluer; Muhammet Burak Batir; Damla Akogullari; Fethi Sirri Çam (Paediatrica Indonesiana, 2022)
Background Renoprotective effects of vitamin D analogues have been shown in several experimental and clinical studies, the exact mechanism of the therapeutic effectiveness of these analogues in Nephrotic syndrome remains unclear, and these are relatively few studies on potential treatment roles for vitamin D analogues in nephrotic-range proteinuria. ?ndicate similar efficacy of the vitamin D analogues calcitriol and paricalcitol in time-limited amelioration of proteinuria in nephrotic syndrome, yet suggest the likelihood of mechanisms other than direct upregulation of nephrin and podocin in podocytes underlie the renoprotective effects of vitamin D analogues. Objective To investigate the effect of vitamin D (Vit D) analogues calcitriol and paricalcitol on urinary protein/creatinine ratio (UPCR) and renal podocin and nephrin expression in a rat model of puromycin aminonucleoside (PAN)-induced nephrotic syndrome (NS). Methods A total of 28 male Wistar Albino rats were separated into 4 groups (n=7 for each) including CON [control; intraperitoneal (IP) saline injection], PAN (NS + IP saline injection), PAN-C (NS + IP 0.4 µg/kg/day calcitriol injection), and PAN-P (NS + IP 240 ng/kg/day paricalcitol injection). Nephrotic syndrome was induced via intravenous (IV) administration of 10mg/100gr PAN. The UPCR as well as histopathological, immuno-histochemical, and real time PCR analyses of kidney tissue specimens were recorded and analyzed among the 4 groups. Results Median UPCR (Day 4) was significantly lower in both the PAN-C [1.45 (range 1.20-1.80)] and PAN-P [1.40 (range 1.10-1.80)] groups than in the PAN group [2.15 (range 2.00-2.40)] (P<0.01 for each). The PAN group had significantly higher mean UPCR than the CON group [1.75 (range 1.40-2.00); P<0.05]. No significant difference in UPCR was noted between groups on Day 7. Median podocin mRNA expression was significantly higher in the PAN-P group compared to the PAN group [22.55 (range 22.42-23.02) vs. 22.06 (range 21.81-22.06), respectively; (P<0.01)]. Conclusion Seven-day calcitriol and paricalcitol supplementation in a rat model of PAN-induced nephrotic syndrome had similar efficacy, in terms of temporary amelioration of proteinuria.